2023
DOI: 10.1080/20008066.2023.2178203
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy for co-occurring gambling disorder and posttraumatic stress disorder in veterans: a narrative review

Abstract: Background: PTSD and gambling disorder (GD) are frequently comorbid. Gambling may provide escape-based coping for the emotions experienced by PTSD sufferers. Military personnel may be at increased risk of PTSD and/or GD. Acceptance and Commitment Therapy (ACT) has been found to improve both PTSD and GD outcomes, yet research into the potential effectiveness of ACT for PTSD and/GD in veterans is scarce. Objective: This review aimed to systematically assess and describe the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“… 17 It is a third-generation contextualism-oriented behavioral therapy that expands the existing cognitive behavioral therapy integrates the connotation of Oriental philosophy, and creatively draws on the concepts of dialectics, spirituality, relationship, and mindfulness. 18 The ACT also maintains an open attitude towards negative and irrational psychological events; that is, patients treat various experiential avoidances with an acceptable attitude and subsequently implement actions on the basis of the existence of pain. The data of this study showed that the EG had overtly higher scores of positive emotion regulation and remarkably lower scores on negative emotion regulation than the CG at T1 and T2, indicating that ACT effectively regulated the cognitive emotion of adolescent patients with NSSI.…”
Section: Discussionmentioning
confidence: 99%
“… 17 It is a third-generation contextualism-oriented behavioral therapy that expands the existing cognitive behavioral therapy integrates the connotation of Oriental philosophy, and creatively draws on the concepts of dialectics, spirituality, relationship, and mindfulness. 18 The ACT also maintains an open attitude towards negative and irrational psychological events; that is, patients treat various experiential avoidances with an acceptable attitude and subsequently implement actions on the basis of the existence of pain. The data of this study showed that the EG had overtly higher scores of positive emotion regulation and remarkably lower scores on negative emotion regulation than the CG at T1 and T2, indicating that ACT effectively regulated the cognitive emotion of adolescent patients with NSSI.…”
Section: Discussionmentioning
confidence: 99%